2014
DOI: 10.1007/s11103-014-0193-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of aerial and subterranean pods development provides insights into seed abortion in peanut

Abstract: The peanut is a special plant for its aerial flowering but subterranean fructification. The failure of peg penetration into the soil leads to form aerial pod and finally seed abortion. However, the mechanism of seed abortion during aerial pod development remains obscure. Here, a comparative transcriptome analysis between aerial and subterranean pods at different developmental stages was produced using a customized NimbleGen microarray representing 36,158 unigenes. By comparing 4 consecutive time-points, totall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 67 publications
(87 reference statements)
6
33
0
Order By: Relevance
“…As to fruit development, it has been applied to strawberry (Aharoni and O’Connell, 2002), tomato (Alba et al, 2005), pear (Fonseca et al, 2004), apple (Lee et al, 2007), and peanut seed development (Zhang et al, 2012; Zhu et al, 2014). But the relationship between calcium and peanut seed at different pods developmental stages was seldom mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to fruit development, it has been applied to strawberry (Aharoni and O’Connell, 2002), tomato (Alba et al, 2005), pear (Fonseca et al, 2004), apple (Lee et al, 2007), and peanut seed development (Zhang et al, 2012; Zhu et al, 2014). But the relationship between calcium and peanut seed at different pods developmental stages was seldom mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of rapid and high-throughput technology for quantification of the transcriptome (Malone and Oliver, 2011) benefited the peanut genomics research, and was used in the seed development and tissue expression of peanut (Zhang et al, 2012; Chen et al, 2013; Wang et al, 2013; Zhu et al, 2014). These researches make it probability to study the relationship of between calcium and peanut pod development by transcriptome method, and explore valuably candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…We found that gynophore GA 4/7 levels significantly decreased after gynophore soil penetration (data not shown). Zhu et al (2014) reported that one to two days of dark treatment significantly decreases the endogenous GA 3 content of gynophores. In the present study, the peanut SPL8 expression level was upregulated in dark-grown S2 (2-fold) and S3 (5-fold) gynophores in comparison with that in S1 gynophores (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Peanut is an important global oil crop and protein source. Peanut plant flowers and finishes pollination above ground as do other plants, while the ovule-carrying peg (gynophore) starts to form above ground and then grows downwards to bury the fertilized ovule in the soil for pod development (Thompson et al, 1985;Xia et al, 2013;Zhu et al, 2014). In this study, we identified 15 potential peanut SPLs that all contained a conserved SBP domain.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al (2013) found that a series of transcripts, including endogenous hormones, respond to optical signals, and that morphogenesis and cell division pathway transcripts showed distinct changes before and after the burying of the gynophore. Zhu et al (2014) compared the transcriptome of the gynophore before and after burying, and described the relevance of changes in expression and hormone levels of GA, IAA, and other hormone-related transcripts. Chen et al (2015) detected 11 transcriptomes from different developmental stages of the gynophore, and exhaustively analyzed the transcripts associated with gravitropism and photomorphogenesis.…”
Section: Introductionmentioning
confidence: 99%